2017
DOI: 10.7717/peerj.3473
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the morphological and biochemical characteristics of Chlorella sorokiniana and Chlorella zofingiensis cultured under photoautotrophic and mixotrophic conditions

Abstract: The responses of two species of microalgae, Chlorella sorokiniana and Chlorella zofingiensis, were compared regarding their morphological and biochemical properties under photoautotrophic and mixotrophic conditions. These microalgae were cultured under both conditions, and their crude ethanolic extracts were examined for their pigment and total phenolic contents. In addition, the microalgae’s antioxidant activities were determined using a DPPH radical scavenging assay and a ferric reducing antioxidant power (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 61 publications
4
43
3
4
Order By: Relevance
“…In a previous report, miR164 was found to regulate chlorophyll breakdown during leaf senescence in Arabidopsis thaliana [ 34 , 35 ] by targeting the no apical meristem, ATAF ½ and cup-shaped cotyledon (NAC) transcription factor involved in chlorophyll catabolism. Similarly, in this study, the chlorophyll content of C. sorokiniana grown under stress-induced conditions was reduced by 80% compared to cultures grown under normal conditions [ 3 ]. These findings demonstrate a possible correlation between the predicted function of the identified miRNA and the morphological study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In a previous report, miR164 was found to regulate chlorophyll breakdown during leaf senescence in Arabidopsis thaliana [ 34 , 35 ] by targeting the no apical meristem, ATAF ½ and cup-shaped cotyledon (NAC) transcription factor involved in chlorophyll catabolism. Similarly, in this study, the chlorophyll content of C. sorokiniana grown under stress-induced conditions was reduced by 80% compared to cultures grown under normal conditions [ 3 ]. These findings demonstrate a possible correlation between the predicted function of the identified miRNA and the morphological study.…”
Section: Discussionmentioning
confidence: 60%
“…Chlorella is known as one of the best microalgae for the production of high-value metabolites such as carotenoids and lipids [ 1 , 2 ]. Microscopic observation of lipid-droplet and starch-granule accumulation in algal cells proved the potential of Chlorella as an alternative source for biofuel production [ 3 ]. Several researchers reported that the manipulation of different environmental factors could affect biochemical production from microalgae [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological characteristics varied noticeably depending on many parameters such as environmental and nutritional represent by cultured media; Azaman et al (2017) proved that mixotrophic cultured medium and light intensity trigger morphological variations among both C.sorokiniana and C. zofingiensis; normal size of C. sorokiniana under standard growth conditions was 2 to 4 mm, and this size doubled when this alga grew under mixotrophic medium and under the higher light intensity with a result of increasing the size to approach even 9 mm due to an increase of cell contents. In another study, George et al (2014) demonstrated several changes in shape and size of cells growing in culture medium under 150 mmol photons; Chokshi et al(2015) have recorded that cells morphology varied due to the introduction of glucose to algae culture medium and the size of these cells increased 1-2 folds regardless of microalgae species.…”
Section: Resultsmentioning
confidence: 99%
“…Saponins generally possess antifungal and antibacterial activities (Feroz 2018). Chlorella sorokiniana contains phenolic compounds that have antioxidant activity (Azaman et al 2017). Chloroform extract of C. vulgaris contains saponins (Adhoni et al 2016;Syed et al 2015), and have antibacterial activity against Staphylococcus aureus, Corynebacterium, Bacillus subtilis, Streptococcus, Salmonella paratyphi B, Klebsiella pneumoniae, Aerobacter aerogenes, Candida albicans, and Aspergillus niger but it showed no growth inhibition against Escherichia coli (Adhoni et al 2016).…”
Section: N U S a N T A R A B I O S C I E N C Ementioning
confidence: 99%